A case report of class II division I malocclusion of Angle treated with cant arc mechanics (Edgewise) - Menéndez Méndez, Leoncio Vladimir (2008)
The present I articulate is developed the procedure of I diagnose and one treatment maloclusion class II division I of Angle, that development in the clinic of post degree of ortodoncia of the faculty of odontolgy of the UNMSM, by means of the technique edgewise, the same one that was created by the Dr. Edward Angle. The clinical case is described by means of the intraoral photographies extra and, the cefalometricos analyses and the obtained results can be evaluated by means of the cefalometricas superpositions, which indicates so much the craneofacial growth as the effects of the treatment.